Turkey’s Foreign Policy Strategy Change in Syrian Crisis (2016-2017) - Luerdi, Luerdi; Alfajri, Alfajri (Jurnal Hubungan Internasional, 2018)
Turkey is one of the important actors whose roles cannot not be ignored in understanding the dynamic of Syrian crisis. Turkey used to interfere the neighboring country in order to remove the Syrian regime by backing the opposition groups and building alliance with the western countries. Turkey began to change its foreign policy strategy in Syria in 2016, but still maintained its domestic security and stability interest. This paper is aimed at explaining the relationship between the driving factors and Turkey’s foreign policy strategy change. This research applied the foreign policy decision making approach where determinants were perceived and acted upon by the official governmental decision makers. James Rosenau’s decision making theory was employed to strengthen the approach, consisting of some foreign policy determinants such as external environment, internal environment, information assessment and decision-making process which further affect decision makers to make the state’s foreign policy decision as the output. The finding of the research showed that domestic and international factors encouraged Turkey to change its foreign policy strategy. Such new strategy was that Turkey was collaborating with Russia in seeking the resolution to create stability within Syria and put an end of the severe conflict.